Biotechnology-Enhanced Poultry Feed: The Potential of Fermented Banana and Cassava Peels as Sustainable Ingredients - Triani, Hera Dwi; Yanti, Gusri; Harly, Resolinda; Amri, M (Journal of Animal Nutrition and Production Science, 2024)
The use of agricultural waste in poultry diets presents a sustainable solution to reduce feed costs and environmental waste. This study investigates the nutritional enhancement of banana peel flour (TKPF) and cassava peel flour (TKSF) through fermentation. The fermentation process significantly improved the crude protein content and metabolic energy of both by-products, with TKPF showing an increase in protein from 7.08% to 11.25% and metabolic energy from 2010 Kcal/kg to 3072.50 Kcal/kg. Similarly, TKSF exhibited a 30.56% increase in crude protein (from 11.84% to 15.46%) and a 68.5% increase in metabolic energy (from 1310 Kcal/kg to 2210 Kcal/kg). Both fermented products also demonstrated a reduction in crude fiber and anti-nutritional factors, making them more digestible and safer for poultry. The findings suggest that fermented banana and cassava peels can be used as cost-effective and environmentally friendly alternatives to traditional feed ingredients in poultry diets.